ANALISIS PENENTUAN INDIKATOR UTAMA PEMBANGUNAN SEKTOR PERTANIAN DI INDONESIA: PENDEKATAN ANALISIS KOMPONEN UTAMA - DERMOREDJO, SAKTYANU K. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 2 Juli 2006, 2012)
One of the main problems in recent agricultural development is difficulty in getting fast, accurate information. This indicators choice is important to guide the government in implementing agricultural development successfully. This paper aims at obtaining the main indicators explaining agricultural development performance. Using PCA (Principle Component Analysis), there were eight main indicators out of 38 variables, namely: (1) irrigated land areas growth (%/year); (2) ratio of rural/urban labor in agricultural sector; (3) ratio of rural/urban labor in non-agricultural sector; (4) Food Security Index (energy and protein) trend; (5) Agricultural sector’s GRDP growth (%/year); (6) Agricultural sector’s share in GRDP (%/year); (7) use of agricultural inputs (seed, fertilizer, and pesticide); and (8) farm business productivity. The results showed that farmers’ incomes and agricultural commodities’ competitiveness (based on export and import trends) were not the main indicators of agricultural development. Therefore, targets of agricultural development are not farmers’ incomes improvement, but farm business productivity improvement through increase in agricultural inputs use.
Keywords: Indicators, Agriculture Sector, Principle Component Analysis